Functionalization and reduction of graphene oxide with p-phenylene diamine for electrically conductive and thermally stable polystyrene composites - Ma, Hui-Ling (2013)
A facile and efficient approach was developed to simultaneously functionalize and reduce graphene oxide (GO) with p-phenylene diamine (PPD) by simple refluxing. This was possible by the nucleophilic substitution reaction of epoxide groups of GO with amine groups of PPD aided by NH3 solution. As a consequence, electrical conductivity of GO-PPD increased to 2.1 × 102 S/m, which was nearly 9 orders of magnitude higher than that of GO. Additionally, after the incorporation of GO-PPD in polystyrene (PS), the composites exhibited a sharp transition from electrically insulating to conducting behavior with a low percolation threshold of 0.34 vol %, which was attributed to the improved dispersion and the reduction of GO-PPD. Thermal stability of the PS/GO-PPD composite was also 8 °C higher than that of PS.